FACTORS RELATED TO THE SUCCESS OF VITAMIN A PROVISION FOR POSTPARTUM MOTHERS IN THE BETUNG PUBLIC HEALTH CENTER IN WORKING AREA, OI REGENCY - Indasari, Bela; Aquari, Bina; Rahmadhani, Sendy Pratiwi; Minata, Fika (STIKES Syedza Saintika Padang, 2025)
Vitamin A functions to increase body resistance, can help restore the mother's health condition in postpartum healing and improve child survival. Consumption of high doses of vitamin A in postpartum mothers become an effective strategy in fulfilling the need for vitamin A for babies through breastfeeding. The purpose of this study was to determine factors related to the success of Vitamin a provision for postpartum mothers in the Betung Public Health Center in working area, Ol Regency in 2024. The study used an analytical survey method and a cross-sectional approach. The population in this study were all postpartum mothers totaling 275 people & sample size was 74 respondents was taken using a purposive sampling technique based on the inclusion & exclusion criteria set. The primary data is collected using a questionnaire and analized using Chi Square test. The results of the study obtained that 39 (53.4%) respondents did not receive vitamin A, 41 (56.2%) had poor knowledge, 38 (52.1%) had high quality health services, and 39 (53.4%) had a role in health workers. Based on the results of Statistical tests, it is known that there was a relationship between knowledge (p value = 0.030), quality of health services (p value = 0.006) and the role of health workers (p value = 0.041) with the Success of Providing Vitamin A to Postpartum Mothers. Keywords: provision of vitamin A to postpartum mothers, knowledge, quality of health services, and the role of health workers